Mathematical model for sustainable optimization in a solid bulk stockyard-port system - da Silva, Arthur Guilherme Siqueira; de Carvalho, Flávio Lúcio Santos; Servare Junior, Marcos Wagner Jesus (Latin American Journal of Energy Research, 2025)
This article addresses the growing shift toward sustainable practices in supply chains, driven by regulatory pressures and increasing consumer awareness. In this context, efficient stockpile allocation and resource optimization become critical to the operational performance of ports. Beyond operational challenges, supply chain management now encompasses significant environmental concerns, particularly the control of CO₂ emissions, underscoring the urgent need for sustainable practices. Within this complex landscape, logistics management is framed as a multi-objective optimization problem aimed at meeting demand, enhancing competitiveness, and minimizing environmental impacts. The core contribution of this study is the development of a mathematical model for the allocation and loading of iron ore in yard-port systems, with a specific focus on minimizing greenhouse gas (GHG) emissions. Computational experiments validate the model’s effectiveness up to instance 14, while instance 15 highlights limitations that indicate the need for alternative approaches. In conclusion, the proposed model serves as a valuable decision-support tool in port supply chains, emphasizing sustainability as a key strategic factor and pointing toward future research directions.
Keywords: Sustainable supply chain; Greenhouse gas emissions (GHG); Stockyard-port system